IMPLEMENTASI AKUNTANSI SEKTOR PUBLIK DALAM SISTEM KEUANGAN PEMERINTAHAN DESA - Erika Rahma Setiyani; Risky Nurfadila (Universitas Tulungagung, 2021)
Abstract The current use of APBD or village funds is required to have efficient financial accountability. Government accounting plays an important role in public sector financial management which is useful in supporting the realization of efficiency and effectiveness in financial management. This study was conducted to analyze the accountability reporting procedures in Gendingan Village. This study is based on the Permedagri concerning Village Financial Management. This research studies about accounting policies, budgeting processes, and the size of the village government's financial transactions which are smaller than the local government. In this study, it was found that the policies implemented by the Gendingan village government had complied with and were carried out in accordance with applicable regulations, then were judged to be accountable in presenting their accountability reports. As well as the existence of a village-based accounting information system (SISKEUDES) to help, village officials are getting more serious in compiling village fund financial accounting reports. Abstrak Penggunaan APBD atau dana desa sekarang ini dituntut untuk mempunyai akuntabilitas keuangan yang efisien. Akuntansi pemerintahan berperan penting dalam pengelolaan keuangan sektor publik yang berguna dalam mendukung terwujudnya efisiensi dan efektifitas dalam manajemen keuangan. Penelitian ini dilakukan untuk menganalisis prosedur pelaporan pertanggungjawaban di Desa Gendingan. Studi ini berlandaskan Permedagri tentang Pengelolaan Keuangan Desa. penelitian ini mempelajari tentang kebijakan akuntansi, proses penganggaran, dan besaran transaksi keuangan pemerintah desa yang lebih kecil dibandingkan dengan pemerintah daerah. Dalam penelitian ini ditemukan bahwa kebijakan yang diterapkan pemerintah desa Gendingan sudah mematuhi dan dijalankan sesuai dengan peraturan berlaku , kemudian dinilai akuntanbel dalam penyajian laporan pertanggungjawabanya. Serta terdapatnya sistem informasi akuntansi berbasis desa (SISKEUDES) membantu, perangkat desa semakin serius dalam menyusun laporan akuntansi keuangan dana desa.